PERANAN TOKOH ADAT SEBAGAI MEDIATOR SOSIAL DALAM MENYELESAIKAN KONFLIK AGRARIA YANG MELIBATKAN MASYARAKAT ADAT MULTIKULTURAL DI INDONESIA (PERSPEKTIF KAJIAN SOCIO LEGAL RESEARCH) - Firman Freaddy Busroh (Universitas Suryakancana, 2017)
ABSTRACTIndonesia is a nation with many islands that consists of traditional society inside. Thattraditional community has a traditional leader who is respected and obeyed to solve theproblem. Customary figures can act as social mediators in solving the problems.Problem solving through social mediation could be more effective and efficient,especially in multicultural societies like Indonesia. Empowering customary law, it canhelp the government in resolving agrarian conflicts.Keywords: Multicultural; Adat leaders; Social Mediator; Community CustomaryLaw; Alternative Dispute Resolution.